What influences antibiotic sales in rural Bangladesh? A drug dispensers' perspective - Mohammad Abdul Matin; Wasif Ali Khan; Mohammad Mahbubul Karim; Sabeena Ahmed; Johannes John-Langba; Osman A. Sankoh; Margaret Gyapong; John Kinsman; Heiman Wertheim (Taylor & Francis Group, 2020)
Background Antibiotic resistance poses a great threat to global health, especially in low- and middle-income countries with a high infectious disease burden and limited resources. In spite of regulations, antibiotics are sold in many settings as non-prescription medicines, resulting in inappropriate use and resistance. Objective This study aimed to investigate the current status of access and use of antibiotics in rural Bangladesh, by exploring the perspectives and sales practices of antibiotic drug dispensers. Methods We used a mixed methods approach (qualitative and quantitative). We mapped and characterized antibiotic purchasing and dispensing sites in the Matlab Health and Demographic Surveillance System catchment area. Furthermore, we investigated the volume of provision of systemic antibiotics in 10 drug outlets. We held 16 in-depth interviews with randomly selected antibiotics dispensers. Interviews explored factors associated with antibiotic selling. Responses were transcribed, coded for themes, and summarized. We used ATLAS.ti 5.2 for conducting a thematic analysis. Results A total of 301 antibiotic dispensers were identified, of whom 92% (n = 278) were private and 8% (n = 23) public. 52% (n = 155) operated informally (i.e. without legal authorization). In order to promote and survive in their business, dispensers sell antibiotics for a range of conditions without a qualified physician's prescription. Factors that facilitate these inappropriate sales include lack of access to healthcare in the rural community, inadequate doctor: population ratio, limited dispenser knowledge, poor pharmacovigilance concerning safety of self medication, lack of enforcement of policies, financial benefits for both customers and dispensers, and high dependency on pharmaceutical companies' information. Conclusion Dispensers in rural Bangladesh sell antibiotics inappropriately by ignoring existing national regulations. They operate the antibiotic sales without facing any legal barriers and primarily with a view to sustain their business, resulting in inappropriate sales of antibiotics to the rural community. The influence of the drug industry needs to be replaced with evidence-based, not commercially driven information. Awareness programs for antibiotic providers that promote understanding of antibiotics and antibiotic resistance through tailored interventions may be helpful in changing current antibiotic sales practices.